Site- and state-selected photofragmentation of 2Br-pyrimidine. Issue 37 (7th October 2015) - Bolognesi, P.; Kettunen, J. A.; Cartoni, A.; Richter, R.; Tosic, S.; Maclot, S.; Rousseau, P.; Delaunay, R.; Avaldi, L.
<x xml:space="preserve">Abstract</x> The fragmentation of the 2Br-pyrimidine molecule following direct valence photoionization or inner shell excitation has been studied by electron–ion coincidence experiments.